Mengatasi Permasalahan Sampah Melalui Sosialisasi dan Pelatihan Budidaya Maggot di Desa Banjarsari - Hermita, Nuniek; Intari, Dwi Esti; Dewi, Amara Syifa; Putri, Chanesa Hestiani; Putri, Dinda Wulandari Hermina; Asqolani, Dini; Ilham, Miftahadi; Destisa, Mutiara; Afrizkialdi, Mochammad Dera; Fathiaturrizkiyah, Nida; Augustien, Putri Shelvi (Civil Engineering for Community Development (CECD), 2024)
This activity is community service through the Student Work Lecture (KKM) program carried out by Group 18 UNTIRTA by making it one of the work programs which is motivated by the relationship between the economic potential of the community, especially in the fisheries sector and the problem of organic waste in Banjarsari Village. To overcome this, by holding outreach and training on maggot cultivation, it is hoped that it can become an innovation and solution to the problem of organic waste and as an alternative to fish food needs in Banjarsari Village. The aim of this activity is to increase public knowledge and awareness of the environment through outreach and training on maggot cultivation as an effort to overcome the waste problem and as an alternative animal feed in utilizing economic potential. In its implementation, the activity method is carried out through socialization and training on maggot cultivation by presenting material and demonstrating how the stages of maggot cultivation are implemented. The result of this activity was that the training participants were enthusiastic about participating in the activities carried out and most of them were able to understand how to implement maggot cultivation. This activity supports the Government's efforts to overcome the existing waste problem. With training on how to cultivate Maggot, it is hoped that it can improve skills, open up employment opportunities, knowledge and care for the environment. So, the people of Banjarsari are interested in entrepreneurship in providing animal feed through Maggot cultivation and can overcome the existing waste problem.